Kratka potopisna besedila Prežihovega Voranca - Bošnjak, Blanka (Jezik in slovstvo, 2010)
From the viewpoint of the indicators of travelogue literature, the short travelogue texts in the collections Od Kotelj do Belih vod (1945) and Borba na tujih tleh (1946) reveal the documentary orientation of the texts along with the subjective presence of the author, who serves to provide information; at the fore are references to social and political life, as well as representations of time and space. In addition to these characteristics of the travelogue journal the texts in both collections also contain various narrative approaches and rhetorically provided real facts, lending them the structural character of the literary travelogue, due to the prevailing aesthetic characteristics and the textual fictional signals the certain texts are approaching narrative prose.
Keywords: Prežihov, Voranc; Slovene literature; slovenska književnsot; travelogue; reportage; potopisi; reportaže; literary travelogue; literarni potopisi; Od Kotelj do Belih vod; Borba na tujih tleh